Remodeling and control of homologous recombination by DNA helicases and translocases that target recombinases and synapsis - Northall, Sarah J; Ivančić-Baće, Ivana; Soultanas, Panos; Bolt, Edward L (MDPI, 2016)
Recombinase enzymes catalyse invasion of single-stranded DNA (ssDNA) into homologous duplex DNA forming "Displacement loops" (D-loops), a process called synapsis. This triggers homologous recombination (HR), which can follow several possible paths to underpin DNA repair and restart of blocked and collapsed DNA replication forks. Therefore, synapsis can be a checkpoint for controlling whether or not, how far, and by which pathway, HR proceeds to overcome an obstacle or break in a replication fork. Synapsis can be antagonized by limiting access of a recombinase to ssDNA and by dissociation of D-loops or heteroduplex formed by synapsis. Antagonists include DNA helicases and translocases that are identifiable in eukaryotes, bacteria and archaea, and which target synaptic and pre-synaptic DNA structures thereby controlling HR at early stages. Here we survey these events with emphasis on enabling DNA replication to be resumed from sites of blockage or collapse. We also note how knowledge of anti-recombination activities could be useful to improve efficiency of CRISPR-based genome editing.